IFRS Mandatory Adoption Effect on the Information Asymmetry: Immediate or Delayed? - Hela Turki; Sonda Wali; Younes Boujelbene (Australasian Accounting, Business and Finance Journal, 2017)
The purpose of this paper is to examine the relationship between the mandatory adoption of IFRS/IAS and the information content of earnings in the European Union. More accurately, this study aims to determine if the effect of IFRS adoption on the level of information asymmetry, apprehended by the cost of capital and the financial analysts’ forecasts, is immediate or delayed. Based on a longitudinal study, we find evidence that for the two first years of adoption, international standards reduces significantly the cost of capital and the dispersion of the financial analysts’ forecasts. Furthermore, the magnitude of this effect increases with increasing the number of years after IFRS adoption. The findings further show that the effect of IFRS adoption on financial analysts’ errors is not immediate and that the errors decrease from the third year following the date of the first adoption. Overall, the findings of this study highlight the importance of adopting IFRS in the reduction of information asymmetry.
Keywords: IFRS; information asymmetry; cost of capital; financial analysts’ forecasts; immediate or delayed effect